Бағалау қызметін құқықтық реттеудегі халықаралық стандарттардың кейбір мəселелері - Қыздарбекова, А.С.; Əсетова, Г.Б. (ҚарМУ баспасы., 2009)
В статье рассматриваются очень актуальные на сегодняшний день международные аспекты правового регулирования оценочной деятельност.. Авторами проводится сравнительный анализ законодательства РК и иностранных государств в сфере оценочной деятельности, формулируются выводы по проблемам внедрения зарубежной практики в национальную систему. There are international aspects of legal regulation of valuation activity in the work. Present relations are very urgent nowadays. In connection with present questions are necessary take into consideration international standarts. That is why in the work merge analys legislation of Republic of Kazakhstan with international country in sphere of valuation activity. As a result of that analys formulates the conclusion of problems inculcation international practice in national system.